Knowledge, awareness, and practices of adverse drug reaction reporting among healthcare professionals in the Ashanti region of Ghana - Emmanuel Delali Kofi Fiagbey; Linda Nyame; Zexiang Bao; Zikomo Gaudence Kipanga; Isaac Nii Lante Lamptey; Daniel Kofi Nyame; Helen Dekyem; Yusuf Nasir Maigari; Andriniaina Eric Abdon; Kwesi Prah Thomford; Jianjun Zou (Indian Journal of Pharmacology, 2026)
Abstract: OBJECTIVES: To assess the knowledge, awareness, and practices of adverse drug reaction (ADR) reporting among healthcare professionals (HCPs) in the Ashanti Region of Ghana and to further identify the predictors of HCPs’ reporting behaviors. METHODS: A cross-sectional survey was conducted among 326 HCPs from various healthcare facilities across the Ashanti Region. Data were collected using structured, pretested questionnaires, and analyzed with R and STATA software, using descriptive statistics and univariate logistic regression to explore the factors associated with reporting behaviors. RESULTS: 93.6% of HCPs were aware of pharmacovigilance (PV), with 85.6% acknowledging ADR reporting as a professional mandate. However, only 49.4% were aware of Ghana’s National Pharmacovigilance Center, with only 50% having submitted fully-filled ADR forms. Barriers to reporting included unavailability of forms (30.3%) and lack of training (23.3%). Age, experience, and previous training significantly influenced reporting ( P < 0.05). The most ADR-implicated drugs were antibiotics (36.5%) and antihypertensives (17.8%), with gastrointestinal (34.4%), and central nervous system (32.4%) manifestations most often reported. CONCLUSIONS: This study reveals relevant insights into the PV landscape in Ghana’s Ashanti Region. Despite high awareness among HCPs in the Ashanti Region, operational knowledge and reporting practice were suboptimal, with most cited barriers being unavailability of forms and lack of training. Our findings highlight the need for targeted interventions such as continuous PV training, improved access to reporting tools, and inclusion of underrepresented HCP cadres like Medical Herbalists to strengthen PV and improve ADR reporting in Ghana.